ANALISA KEBUTUHAN JEMBATAN PENYEBERANGAN ORANG DI KOTA BANDAR LAMPUNG, LAMPUNG - Aditya Mahatidanar Hidayat (Jurnal Teknik Sipil, 2018)
The  existence  of  pedestrians  would  need  the  facility  for  pedestrians,    crossing  street  as  the  people crossing  bridge  (  bridge  ),  where  the  bridge  mounted  when  required  no  a  meeting  between  the  current walkers  and  traffic  flow.That  pedestrians  want  to  use  bridge  must  all  be  ensured  security  and  distance increased are not going too far.The purpose of this research is analyzing the needs of the people crossing bridge  in  the  way  of  legal  because  lampung  city  based  on  the  calculation  on,  the  volume  of  vehicles highest  a  month  8539  junior  /  hours  with  the  403  waders  per  hour  him  and  speed  rata-rata  28,4  km  / hours.With  the  data  collected  and  based  on  the  results  of  the  analysis  representing  day  and  rush  hour road users in one week and in concluded clearly that it is supposed at roads legal because precisely in front of Pasar Koga and Advent Hospital built bridge people to pedestrian